PERILAKU WANITA PEKERJA SEKSUAL (WPS) DALAM MELAKUKAN SKRINING INFEKSI MENULAR SEKSUAL (IMS) DI LOKALISASI TEGAL PANAS KABUPATEN SEMARANG - Susmiati, Riki; Shaluhiyah, Zahroh; Riyanti, Emmy (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Screening for Sexually Transmitted Infections ( STI ) is one of STI management program in group sex workers. During 2014 , from 278 visits to the health center Bergas, there were 11 people diagnosed with bacterial vaginosis positive and 90 positive servitis. Localization of Tegal panas has the lowest number of screening visits among other localization in Semarang district. The purpose of this study to analyze the behavior of Female Sexual Workers ( FSWs ) in STI screening in Localization Tegal panas Regency Semarang. This research is quantitative with cross sectional approach. A total of 109 respondents from a total population of 120 people. Analyzed using univariate and bivariate analysis. The results of this study indicate that as many as 70,6 % of respondents did not do the screening. Factors associated with screening behavior is age with p-value 0,002, long working with p-value of 0,005, and the support pimps with p-value 0,001. Factors not associated with screening behavior is education, knowledge, attitudes, perceptions of screening services, behavioral friends, and support health workers. From this study it can be concluded that there is a relationship between age, long working and support pimps with FSWs behavior in STI screening. Suggestions for Localization board Tegal panas that there are stricter regulations related to the behavior of female sex workers in following the screening.